Can Asia sustain an export-led growth strategy in the aftermath of the global crisis? An empirical exploration - Arslan Razmi; Gonzalo Hernandez (Asian Development Bank Institute (ADBI), 2011)
Many developing countries have attempted to pursue the East Asian growth model in recent decades. This model is widely perceived to have been based on export-led growth. Given that developed countries are likely to grow at a slower rate and be less willing to run trade deficits in the post-financial-crisis world, can this growth model be sustained? Using panel data for Asian countries, this paper contributes to addressing this question by distinguishing between different kinds of export- and tradable-led growth in order to more precisely identify the nature of growth in the pre-crisis decades. We find in particular that, among our variables of interest, the proportion of a country's manufactured exports that is destined for industrialized countries is the one most robustly associated with output growth. The results have implications for continued post-crisis growth in Asian developing countries.
Keywords: F43; O11; O53; 330; Exportinduziertes Wachstum; Wirtschaftspolitisches Ziel; Finanzmarktkrise; Wirtschaftskrise; Makroökonomischer Einfluss; Wirtschaftswachstum; Entwicklungsländer; Asien